IMPLEMENTASI PROGRAM ADIWIYATA (STUDI PADA SMP NEGERI 20 PEKANBARU) - Susi J. Silaban; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
SMPN 20 PEKANBARU have a high level of cares and also participatives side by whole the school citizen to take care the environment. Also with the work program which is runs on as maximum as possible for the satisfied outcome to the school citizen.The purposes of this research were to find out the implementation of adiwiyata program and to find out the factors which influence the implementation of adiwiyata program. This research using the implementation theory concept which is stated by Syukur in Sumayadi. This research also using qualitative approach by the collecting interview datas technique, observation and documentation.Based on the research result through interview and observation, that’s find that implementation of adiwiyata program in SMPN 20 PEKANBARU has been effective. This things could be observe based on the goal of the work program as the indicator of adiwiyata program. The factor that influences of implementation adiwiyata program are facilitates, participation of the school citizen and financial of the school.Key words: Implementation, Program, Adiwiyata